Effect of multiple-dose regimens of cyclooxygenase inhibitors and their combinations with mexidol on behavior in mature rats - E. A. Ivanova; A. G. Vasilchuk; A. I. Matyushkin; T. A. Voronina (Фармакокинетика и Фармакодинамика)
Effects of multiple-dose regimens (oral, daily, once a day for 15 days) of cyclooxygenase (COX) inhibitors etoricoxib (1 and 10 mg/kg), diclofenac sodium (1 and 5 mg/kg) and their combinations with 2-ethyl-6-methyl-3-hydroxypyridine succinate (mexidol 25 mg/kg) on rat behavior were studied in the open field test, rotarod test and elevated plus maze test. Exploratory (in open field test) and locomotor (in rotarod test) behavior of rats was significantly weakened only by the non-selective COX inhibitor diclofenac sodium at 5 mg/kg, which is due to the peripheral side effect of the drug. The selective COX-2 inhibitor etoricoxib increased the time in the central area of the elevated plus maze at 1 and 10 mg/kg and reduced the latent period of locomotion in the open field test at 10 mg/kg. A combination of diclofenac sodium (1 mg/kg) with mexidol neither reduced exploratory behavior nor caused motor deficit in contrast to diclofenac sodium at 5 mg/kg. However, a combination of etoricoxib (1 mg/kg) with mexidol inhibited locomotor activity in the rotarod test. Nevertheless, it produced no significant effects on the exploratory behavior or anxiety of animals in the open field test and elevated plus maze test.